2017
DOI: 10.1186/s13071-017-2427-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiopulmonary and inflammatory markers in dogs with heartworm infection during treatment with the 2014 American Heartworm Society recommended treatment protocol

Abstract: BackgroundHeartworm disease in dogs is a life-threatening parasitic disease. Although adulticide treatment with melarsomine has been proven to be the most effective, complications associated with adulticide treatment are major concerns for clinicians.MethodsThis study evaluated the change in levels of D-dimer, interleukin-6, C-reactive protein and cardiac troponin I in 12 dogs with different severities of heartworm infection treated by the American Heartworm Society (AHS) recommended protocol during the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A striking increase in CRP and decrease in albumin and paraoxonase-1 activity have been observed in canine heartworm disease [ 22 ]. CRP levels are elevated in canine heartworm disease because of inflammation involved in the pathogenesis [ 23 ]. Heartworm disease leads to pulmonary hypertension and, in the late stage, may induce right-side cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A striking increase in CRP and decrease in albumin and paraoxonase-1 activity have been observed in canine heartworm disease [ 22 ]. CRP levels are elevated in canine heartworm disease because of inflammation involved in the pathogenesis [ 23 ]. Heartworm disease leads to pulmonary hypertension and, in the late stage, may induce right-side cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…One dog had asymptomatic heartworm disease, considered Stage I, and not treated at the time of sample collection. An investigation of inflammatory markers in dogs with heartworm disease that IL‐6 was not increased compared to normal dogs at the time of diagnosis, and increased following therapy (Yoon et al., ). Based on this data, the impact of untreated Stage I heartworm disease in one dog in this study is expected to be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers have been used as a measure of the severity of cardiopulmonary changes in HWD (61,(101)(102)(103)(104). These have not been measured during moxi-doxy treatment but were assessed in dogs given IVM-doxy (61).…”
Section: Referencesmentioning
confidence: 99%
“…This was more frequently the case for dogs with Class 3 HWD ( 61 ). In both studies, dogs treated with melarsomine showed significant reductions in biomarkers over the course of treatment, with improvements considered to be markedly better than for IVM-doxy (a direct comparison was not performed) ( 61 , 104 ). These findings support other evidence that less cardiopulmonary damage occurs in melarsomine-based treatment protocols.…”
Section: Safety Welfare and Population Concernsmentioning
confidence: 99%